A Guide to Operational Impact Analysis of Variable Renewables : Application to the Philippines - World Bank (Washington, DC, 2014)
This document serves as a guide for those wishing to investigate the impacts of variable renewable energy (VRE) on the operation of power systems, particularly in the Philippines. The work was commissioned by the World Bank in 2011 to enhance the understanding of power system operation issues most affected by the integration of VRE, based on international experience. The objective is to build capacity in the Philippines for determining the important issues for the national grid and to enable the Philippines to design, carry out, and interpret the results of appropriate and effective studies. The approaches presented in this guide are based on state-of-the-art international practices, adapted to suit local conditions in the Philippines. The guide was developed through a survey of international VRE integration studies, charting the relevance to the Philippines of key elements such as the physical structure of the power system, the energy mix, expected level of VRE penetration, market structure, and operation practices and standards. The study guide shows how to estimate the amount of VRE that can be integrated into the power system if no changes are made to its present configuration; however, more important, it shows how to determine the potential operational impacts if a certain percentage of renewable energy resources are to be integrated. The main modeling approaches, data requirements, and scenarios that need to be analyzed to assess different types of impacts are described, and are supported by summaries of relevant international experience and key reference studies.